2020
DOI: 10.1055/s-0040-1701543
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of Gutta-Percha-, Sealer-, and Void-Filled Areas in Oval-Shaped Root Canals Obturated with Different Filling Techniques: A Confocal Laser Scanning Microscopy Study

Abstract: Objective This study compared different obturation techniques, analyzing percentage of areas filled with gutta-percha, sealer, and voids (PGFA, PSFA, and PVFA, respectively) in oval-shaped root canals. Materials and Methods A total of 60 extracted human mandibular central incisors were decoronated, instrumented, and irrigated using the same protocol. After drying, the root canal was filled with AH Plus labeled with 0.1% rhodamine B dye using a Lentulo spiral. The filling procedure was performed by dividing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…CHC and cold lateral compaction are known to increase void occurrence compared to warm gutta-percha obturation techniques, especially in large and oval canals regardless of the type of sealer [ 103 , 105 , 122 , 123 ]. However, in case of narrow, long, and curved canals, the use of warm vertical compaction can be questionable, since penetration of the heat plugger at the appropriate level (4 mm short of the working length) can sometimes be impossible.…”
Section: A Proposal For Clinical Perspectives On Csbs With Cold Hydraulic Condensationmentioning
confidence: 99%
“…CHC and cold lateral compaction are known to increase void occurrence compared to warm gutta-percha obturation techniques, especially in large and oval canals regardless of the type of sealer [ 103 , 105 , 122 , 123 ]. However, in case of narrow, long, and curved canals, the use of warm vertical compaction can be questionable, since penetration of the heat plugger at the appropriate level (4 mm short of the working length) can sometimes be impossible.…”
Section: A Proposal For Clinical Perspectives On Csbs With Cold Hydraulic Condensationmentioning
confidence: 99%
“…[33][34][35] It is suggested by the authors that the flow ability and the dimensional stability of this sealer positively affected the filling sealability. [33][34][35][36]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the imags obtained by CLSM allows a quantitative data, unlike the qualitative scores commonly used in SEM imags, which may provide less reliability [26]. Rhodamine B dye is the standard fluorophore dye used, and it has been previously demonstrated that your use of in low concentrations (0.1%) did not change the sealer properties, especially with epoxy resin-based sealer [6,27] .…”
Section: Discussionmentioning
confidence: 99%
“…Diapro-seal (Diadent -Korea) was maniputed according to the manufacturer's instructions. Fluorescent rhodamin B dye (Sigma Aldrich, MO, USA) was added to the sealer mixture at a concentration of 0.1% [6] to allow visualization under a confocal laser microscope (Olympus, Tokyo, Japan). Size 30 rotary lentalo spiral was used for a uniform sealer distribution [Dentsply Maille Switzerland].…”
Section: Root Canal Fillingmentioning
confidence: 99%